2018
DOI: 10.1002/adom.201800570
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Electromagnetically Induced Transparency in a Terahertz Metamaterial Array with Graphene for Continuous Resonance Frequency Tuning

Abstract: Optoelectronic terahertz modulators, operating by actively tuning metamaterial, plasmonic resonator structures, have helped to unlock a myriad of terahertz applications, ranging from spectroscopy and imaging to communications. At the same time, due to the inherently versatile dispersion properties of metamaterials, they offer unique platforms for studying intriguing phenomena such as negative refractive index and slow light. Active resonance frequency tuning of a metamaterial working in the terahertz regime is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 51 publications
1
68
1
Order By: Relevance
“…Therefore, since the length of the slot antenna varies, the resonant frequency can be adjusted as desired (Figure 6c). Therefore, it is possible to control the optical characteristics of the metamaterials by adjusting its dielectric properties by thermal, [65] electrical [66] or optical stimulus. In these slot antennas, greater field intensity can be localized at the center as the width of the slot decreases to allow the same amount of light to pass through (Figure 6d).…”
Section: Terahertz Metamaterials and Their Optical Characteristicsmentioning
confidence: 99%
“…Therefore, since the length of the slot antenna varies, the resonant frequency can be adjusted as desired (Figure 6c). Therefore, it is possible to control the optical characteristics of the metamaterials by adjusting its dielectric properties by thermal, [65] electrical [66] or optical stimulus. In these slot antennas, greater field intensity can be localized at the center as the width of the slot decreases to allow the same amount of light to pass through (Figure 6d).…”
Section: Terahertz Metamaterials and Their Optical Characteristicsmentioning
confidence: 99%
“…Considering the manufacturing process, the chip can be feasibly fabricated by means of conventional techniques. The fabrication of the chip is divided into four steps, roughly: Firstly, grow metallic structures on the front and back surfaces of the silicon/silicon dioxide (SSD) wafer using photolithography and lift-off process [3]; secondly, the photoresist patterns and the metallic structures together serve as a mask during the reactive ion etching (RIE) of the unneeded silica structures on both sides of the SSD wafer [30]; thirdly, transfer the graphene to both sides of the chip and then pattern the graphene strips using e-beam lithography and etching with a radio frequency oxygen plasma asher [19]; finally, connect the electrodes to the external voltage source through leads [19].…”
Section: Device Design and Simulationmentioning
confidence: 99%
“…Graphene-based metamaterials used as waveguides [15], switches [16] and sensors [17] have shown their potential in developing optical devices. Meanwhile, the THz devices integrated with graphene emerged the probability in active control: Li et al experimentally demonstrated an active diode for the THz waves consisting of a graphene-silicon hybrid film [18], and Kindness et al achieved active resonance frequency tuning of a THz metamaterial by integrating metal-coupled resonator arrays with electrically tunable graphene [19]. Active devices are gradually being brought to the forefront of THz applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optical tuning method requires pump laser‐based sophisticated experimental setups, while the MEMS‐based tuning method requires complex fabrication processes. Hence, electrically controllable EIT metamaterials have attracted attention as an alternative method to realize active EIT systems for practical applications …”
mentioning
confidence: 99%